Α Comparison of Physical Activity Patterns and Physical Self-Perception in Obese and non-Obese Children - Tzetzis, Γιώργος; Kakamoukas, Βασίλης; Goudas, Μάριος; Tsorbatzoudis, Χαράλαµπος (Inquiries in Physical Education and Sport, 2005)
The purpose of the present study was the comparison of physical activity (PA) patterns and physical self-perception, in obese and non-obese children. The sample consisted of 35 non-obese and 34 obese seventh grade children. Objective measurements of PA were collected over a 4-day period using the CSA 7164 accelerometer and specifically a): total daily counts b) daily moderate (3-5,9 METs) physical activity (MVPA) and c) daily vigorous physical activity (≥ 6 METs, VPA). Self-Perception of body appearance, and athletic competence were measured by Harter’s (1985) Self-perception Profile for Children. Compared to their non-obese counterparts, obese children exhibited significantly lower daily accumulations of total daily counts, MVPA, and VPA. Obese children reported significantly lower levels of physical self-perception. The results are consistent with the results of previous research (Rowlands et al., 1999; Trost et al., 2001) suggesting that physical inactivity is an important contributing factor in the maintenance of childhood obesity. Interventions and the organization of systematic practice and counseling for obese and non-obese children will promote PA and reinforce positively their self-perception.